Health risk management for safe vegetable irrigation - Drechsel, Pay; Keraita, Bernard N.; Amoah, Philip; Karg, H. (2014)
This chapter presents approaches tested in Ghana to mitigate wastewater irrigation-related risks for consumers and farmers from microbial contamination. The recommended interventions follow the WHO approach concerning multiple barriers along the food chain. Factors that could support the uptake of safety measures are discussed.